Use of gps and radiosonde data for estimating water vapour attenuation on satellite-earth links - Abdul Sukor, Jumadi (2004)
Water vapour is one of the critical components of the earth's atmosphere. It has a significant attenuation effect at millimeter wavelength [I], as well as plying a key role in the global climate system [2]. Water vapour attenuation has been positively correlated with cloud attenuation [3], Therefore, it is important that the amount of water vapour in the atmosphere is quantified accurately for radiowave propagation studies. Atmospheric scientists have developed a variety of means to measure the vertical and horizontal distribution of water vapour. Two established techniques for the measurement of water vapour are through the use of radiosondes and water vapour radiometers (WVR). However, each technique has its own specific limitations to the measurement of water vapour. The use of global positioning system (GPS) to measure water vapour is a relatively new technique and also overcomes some of the limitations of the two established techniques described above. Therefore, the objective of this research project is to propose the use of GPS as a new approach of tool to measure water vapour. Hence, the water vapour attenuation can be obtained from ITU-R (Rec. ITUR P.676-4). This study is focused to compare between the result of Integrated Water Vapour (IWV) obtained from Radiosonde data and GPS data for several stations in Malaysia. Thus stations which have been selected for this study namely, Kuala Lumpur, Kota Bahru Kelantan, Pulau Pinang, TaWau Sabah and Kota Kinabalu Sabah. An analysis based on the IWV obtained from GPS data and Radiosonde data is then performed to analyze the error of IWV between them. This analysis of error was used two methods called Root Means Square Error (RMSE) and Mean Absolute Percentage Error (MAPE). RMSE is used to estimate the level of accuracy of IWV obtained from GPS data compared with the IWV obtained from Radiosonde data. The smaller of its value means the higher of the accuracy. In other hands, although MAPE is also used to demonstrate the error but the error will show in terms of percentage. The balance of this percentage of error will show the reliability or accuracy in percentage of IWV obtained from GPS data compared with the IWV obtained from Radiosonde data. The result of the analysis shows that the difference of RMSE mostly less than 10 mm for all the selected stations in Malaysia. The water vapour attenuation caused by the amount error of 10 mm is about 0.01276 dB at 12 GHz and 0.12766 dB at 20 GHz. The percentage of error which is resulted from MAPE method is less than 10%. This result indicated that the accuracy or reliability to estimate waer vapour by using GPS technique is mostly 90% and above compared with the use of Radiosonde Technique. It can be concluded that there is a big potential on prediction of Water Vapour Attenuation by using GPS system.